EXPLORING THE ROLE OF PARENTAL PRESSURE IN SHAPING ADOLESCENT PSYCHOLOGICAL AND SUBJECTIVE WELL-BEING IN MUZAFFARPUR DISTRICT BIHAR - Kumar, Vinay; Kumar, Krishna (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Background: Adolescence is a formative developmental stage where external factors, particularlyfamily dynamics such as parental pressure, significantly influence psychological andsubjective well-being. In India, the socio-cultural emphasis on academic achievementoften intensifies such pressure, but localized evidence, especially fromregionslikeMuzaffarpur, Bihar, remains scarce. Objective: To examine the influence of parental pressure on the psychological and subjectivewell-being of adolescents in Muzaffarpur district, Bihar, and to assess perceptual differences based on gender. Methods: A cross-sectional survey was conducted among 400 adolescents (200 males, 200 females), aged 15–21 years, using three standardized instruments: the Parental Pressure Scale (PPS), Psychological Well-Being Scale (PWBS), and SubjectiveWell- Being Scale (SWBS). Descriptive statistics, t-tests, Pearson correlations, andlinearregression analyses were performed using SPSS software. Results: Findings indicated moderate to high parental support (Mean PPS = 138.1), relativelyhigh psychological (Mean PWBS = 187.0) and social well-being (MeanSWBS=191.15). Males reported significantly higher social well-being (p = 0.023), whilenosignificant gender differences were found in psychological well-being or perceivedparental pressure. Regression analysis revealed that perceived parental support isastrong predictor of psychological well-being (R² = 0.361) and a moderate predictor ofsocial well-being (R² = 0.115). Conclusion: Parental expectations play a vital role in shaping adolescent mental health. Whilesupport can foster resilience and emotional health, excessive academic pressuremay diminish subjective well-being. Gender differences in social well-beinghighlightthe need for gender-sensitive parental engagement strategies.